Small bowel video capsule endoscopy: an overview. (May 2013) - Mustafa, Barzin F; Samaan, Mark; Langmead, Louise; Khasraw, Mustafa
Video capsule endoscopy (VCE) is being increasingly used to investigate small bowel pathology. It is the gold standard for obscure gastrointestinal bleeding and iron deficiency anemia. VCE has been in use since 2001 and indications for its use are expanding. VCE is also a useful diagnostic tool in small bowel Crohn's disease, celiac disease, surveillance of polyps, small bowel malignancy and drug-induced small bowel injury. Although VCE is considered a safe and easy procedure, there are a few limitations. These include cost, capsule retention and inability to take a biopsy and perform any therapeutic maneuvers. Contraindications for VCE include pregnancy, patients with a swallowing disorder, history of previous abdominal surgery or concurrent abdomino–pelvic irradiation. This is an overview of VCE, its role and indications in clinical practice, potential complications and contraindications, as well as the ongoing and expected advances in the field.